Busana Wayang Orang Tokoh Bima Sebagai Inspirasi Desain Busana Pengantin Wanita Modern - Bestari, Afif Ghurub (Prosiding Pendidikan Teknik Boga Busana, 2021)
This paper titled Bima’s Costum Inspires Modern Bridal Design is aimed at: First, giving alternative bridal design to the modern bridal. Secondly, conditioning Indonesian people so as to be able to appreciate their cultural heritage, particularly the traditional arts. Third, popularising an Indonesian arts, especially Bima’s Costum, which has been already adapted in international style for long. The process of designing international bridal which in inspired by the Bima’s costum takes two steps. The preparation includes: the source of inspiration, collecting references, selecting media and drawing tools, improving basic ideas, deciding colours, material, silhouette, and the details of the clothing. The making includes: global sketching as alternatives for drawing the designs, selecting sketches, details drawing of the design, from the light effect, on the drawing, the putting thickness of the material, up to describing details of the accent and colouring. Finally, we can visualize on international bridal inspired by the traditional Bima’s Costum which is ready to wear. On the conclusion, the variety of traditional bridal in Indonesia gives big and significant contributions to the development of modern bridal.